2002
DOI: 10.1002/gcc.10038
|View full text |Cite
|
Sign up to set email alerts
|

Double minute chromosomes in acute myeloid leukemia and myelodysplastic syndrome: Identification of new amplification regions by fluorescence in situ hybridization and spectral karyotyping

Abstract: Double minute chromosomes (dmin) are small chromatin bodies consisting of genes amplified in an extrachromosomal location. dmins are uncommon in hematologic malignancies; they are seen primarily in acute myeloid leukemia, with amplification of the MYC oncogene or, less frequently, the MLL transcription factor. Nine patients with hematologic malignancies with dmin were seen at the Roswell Park Cancer Institute between 1985 and 2000; eight had acute myeloid leukemia and one a myelodysplastic syndrome. Fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 34 publications
(39 reference statements)
2
28
0
Order By: Relevance
“…FISH studies have revealed the genes involved in the amplified regions. Amplifications of the MYC and MLL genes have been previously reported in acute myeloid leukemia (AML), [2][3][4] and of AML1 and MLL in ALL. 3,5 Although amplification of the BCR/ABL fusion gene has been described in cases of chronic myeloid leukemia (CML) treated with imatinib mesylate, seen both as HSRs 6 and dmins, 7 amplification of ABL alone is rare.…”
Section: To the Editormentioning
confidence: 95%
See 1 more Smart Citation
“…FISH studies have revealed the genes involved in the amplified regions. Amplifications of the MYC and MLL genes have been previously reported in acute myeloid leukemia (AML), [2][3][4] and of AML1 and MLL in ALL. 3,5 Although amplification of the BCR/ABL fusion gene has been described in cases of chronic myeloid leukemia (CML) treated with imatinib mesylate, seen both as HSRs 6 and dmins, 7 amplification of ABL alone is rare.…”
Section: To the Editormentioning
confidence: 95%
“…3 Finally, multiple studies show statistically significant reductions in relapse rates in patients who develop acute GVHD, chronic GVHD or both. 4 Unfortunately, the efficacy of a GVL effect in the context of DLI for ALL relapse post-transplant is quite unimpressive. One…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Deleterious mutations of PRDM1 associated with loss of BLIMP1 protein have also been reported in primary central nervous system lymphoma 63 . Finally, ETS-1, the transcription factor, which is amplified in certain leukemias, interacts with BLIMP1 leading to a block in BLIMP1 DNA binding activity and a reduction in the ability of BLIMP1 to repress target genes [64][65][66][67][68] . In contrast, the over-expression of the BLIMP1β isoform has been reported in multiple myeloma, DLBCL and in some T cell lymphomas 6,[69][70][71] .…”
Section: Blimp1 Is a Tumour Suppressor Genementioning
confidence: 99%
“…68,69 MYC amplification in AML is infrequent, although double minute (dmin) chromosomes and homogeneous staining regions (hsr) including the region 8q24, where MYC maps, have been described in AML. 70,71 MYC overexpression in AML induced resistance to chemotherapeutic drugs. 72 Increased MYC levels were correlated with decreased microRNA-29 family expression in AML.…”
Section: Acute Myeloid Leukemiamentioning
confidence: 99%